Methodological basics for evaluating the economic efficiency of the reconstruction of residential buildings - Lysytsia, N.; Husarova, L. (Ways to Improve Construction Efficiency, 2023)
Modern approaches to the implementation of complex programs for the reconstruction of residential buildings are analyzed. The need to take drastic decisions and measures aimed at improving the current situation with the technical condition of residential buildings in the country has been proven. The advantages of reconstruction of buildings over new construction are given, since it is expedient to organize the reconstruction of the housing stock through the demolition of old objects and new construction in cases where the high level of physical wear and tear of residential buildings does not allow the effective use of capital investments of owners and funds of state support for reconstruction works. In addition, the demolition of old buildings, design, preparation of the territory and the construction itself significantly increase the time of commissioning and the cost of the future building. The technical and economic indicators (TEP) during the construction of buildings and structures, which are calculated for comparing constructive and volume-planning solutions and choosing the most economically advantageous of them, are considered. The system of indicators is analyzed, which is based on the determination of the relative technical and economic efficiency of the reconstruction of a residential building and reflects the ratio of the entire set of costs associated with the reconstruction and the results achieved during the construction, installation and repair works. The full volume of costs was analyzed when calculating the volume of capital investments aimed at improving living conditions (for example, improving the thermal insulation of enclosing structures, installing additional engineering communications and replacing outdated equipment, re-planning of apartments), costs associated with increasing the living space by increasing storeys of the building, as well as the costs of relocating residents, observing the norms of providing living space and providing the necessary social infrastructure. To determine the effectiveness of a specific residential building reconstruction project, costs and revenues from the implementation of the project are planned. By income, we mean proceeds from the sale of housing, renting out premises for offices and other types of commercial activities, as well as utility payments.